Detection of heterogeneous vancomycin intermediate resistance in MRSA isolates from Latin America (2020)
Background:Vancomycin is a common first-line option for MRSA infections. The heterogeneous vancomycin-intermediateStaphylococcus aureus(hVISA) phenotype is associated with therapeutic failure. However, hVISAisolates are usually reported as vancomycin susceptible by routine susceptibility testing procedures.Objectives:To detect and characterize the hVISA phenotype in MRSA isolates causing infections in nine LatinAmerican countries.Methods:We evaluated a total of 1189 vancomycin-susceptible MRSA isolates recovered during 2006–08 and2011–14. After an initial screening of hVISA using glycopeptide-supplemented agar strategies, the detection ofhVISA was performed by Etest (GRD) and Macro-method (MET). Isolates deemed to be hVISA were subjectedto population analysis profile/AUC (PAP/AUC) and WGS for further characterization. Finally, we interrogatedalterations in predicted proteins associated with the development of the VISA phenotype in both hVISA andvancomycin-susceptibleS. aureus(VSSA) genomes.Results:A total of 39 MRSA isolates (3.3%) were classified as hVISA (1.4% and 5.6% in MRSA recovered from2006–08 and 2011–14, respectively). Most of the hVISA strains (95%) belonged to clonal complex (CC) 5. Only6/39 hVISA isolates were categorized as hVISA by PAP/AUC, with 6 other isolates close (0.87–0.89) to the cut-off(0.9). The majority of the 39 hVISA isolates exhibited the Leu-14!Ile (90%) and VraT Glu-156!Gly (90%) aminoacid substitutions in WalK. Additionally, we identified 10 substitutions present only in hVISA isolates, involvingWalK, VraS, RpoB and RpoC proteins.Conclusions:The hVISA phenotype exhibits low frequency in Latin America. Amino acid substitutions in proteinsinvolved in cell envelope homeostasis and RNA synthesis were commonly identified. Our results suggest thatEtest-based methods are an important alternative for the detection of hVISA clinical isolates.